Shedding light on ethylene metabolism in higher plants - Rodrigues, Maria A.; Bianchetti, Ricardo E.; Freschi, Luciano (Frontiers in Plant Science, 2014)
Ethylene metabolism in higher plants is regulated by a wide array of endogenous and environmental factors. During most physiological processes, ethylene levels are mainly determined by a strict control of the rate-limiting biosynthetic steps responsible for the production of 1-aminocyclopropane-1-carboxylic acid (ACC) and its subsequent conversion to ethylene. Responsible for these reactions, the key enzymes ACC synthase and ACC oxidase are encoded by multigene families formed by members that can be differentially regulated at the transcription and post-translational levels by specific developmental and environmental signals. Among the wide variety of environmental cues controlling plant ethylene production, light quality, duration and intensity have consistently been demonstrated to influence the metabolism of this plant hormone in diverse plant tissues, organs and species. Although still not completely elucidated, the mechanisms underlying the interaction between light signal transduction and ethylene evolution appears to involve a complex network that includes central transcription factors connecting multiple signaling pathways, which can be reciprocally modulated by ethylene itself, other phytohormones, and specific light wavelengths. Accumulating evidence has indicated particular photoreceptors as essential mediators in light-induced signaling cascades affecting ethylene levels. Therefore, this review specifically focuses on discussing the current knowledge of the potential molecular mechanisms implicated in the light-induced responses affecting ethylene metabolism during the regulation of developmental and metabolic plant responses. Besides presenting the state of the art in this research field, some overlooked mechanisms and future directions to elucidate the exact nature of the light-ethylene interplay in higher plants will also be compiled and discussed.